Devisable POM/Ni Foam Composite: Precisely Control Synthesis toward Enhanced Hydrogen Evolution Reaction at High pH. Issue 68 (4th November 2019) - Jia, Xueying; Streb, Carsten; Song, Yu‐Fei
Abstract: Polyoxometalates (POMs) are promising catalysts for the electrochemical hydrogen production from water owing to their high intrinsic catalytic activity and chemical tunability. However, poor electrical conductivity and easy detachment of the POMs from the electrode cause significant challenges under operating condition. Herein, a simple one‐step hydrothermal method is reported to synthesize a series of Dexter–Silverton POM/Ni foam composites (denoted as NiM ‐POM/Ni; M =Co, Zn, Mn), in which the stable linkage between the POM catalysts and the Ni foam electrodes lead to high activity for the hydrogen evolution reaction (HER). Among them, the highest HER performance can be observed in the NiCo‐POM/Ni, featuring an overpotential of 64 mV (at 10 mA cm −2, vs. reversible hydrogen electrode), and a Tafel slope of 75 mV dec −1 in 1.0 m aqueous KOH. Moreover, the NiCo‐POM/Ni catalyst showed a high faradaic efficiency ≈97 % for HER. Post‐catalytic of NiCo‐POM/Ni analyses showed virtually no mechanical or chemical degradation. The findings propose a facile and inexpensive method to design stable and effective POM‐based catalysts for HER in alkaline water electrolysis. Abstract : HER evolution : A series of Dexter–Silverton‐type NiM ‐POMs on Ni foam electrodes has been successfully deposited for HER in alkaline media. Among them, the NiCo‐POM/Ni exhibited the best performance with low overpotential of 64 mV and Tafel slope of 75 mV dec −1 at current density of 10 mA cm ‐2 .